Use of Resin-Based Provisional Material to Create the Posterior Palatal Seal in Complete Denture Definitive Impressions - de Souza Batista, Victor Eduardo; Vechiato-Filho, Aljomar José; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP] (Wiley, 2017)
The purpose of this article was to present an alternative procedure using resin-based provisional material to create the posterior palatal seal (PPS). This method offers more practicality in clinical routine and increased control for addition of material to create the PPS when compared to traditional techniques such as the use of impression wax.
Keywords: Dental impression materials; Dental impression technique; Dentures